Phytochemical Profiling and in Vitro Antitrypanosomal Efficacy of the Aqueous Leaf Extract of Combretum glutinosum (L.) Against Trypanosoma brucei - Abdullahi, Raihana Idris; Madu, Hadiza Clark; Ibrahim, Nafiu Muhammad; Suleiman, Ibrahim; Yahaya, Adama; Mijinyawa, Abdullahi; Wada, Yunusa A. (FUDMA Journal of Sciences, 2026)
African trypanosomiasis, a severely neglected tropical disease, is persistently plagued by a limited arsenal of therapeutic options that are frequently associated with high toxicity and emerging resistance. This study systematically investigated the phytochemical composition and the in vitro antitrypanosomal potential of an aqueous leaf extract of Combretum glutinosum against Trypanosoma brucei. Fresh leaves were collected, shade-dried, and extracted via maceration in distilled water. Qualitative phytochemical analysis confirmed the presence of diverse secondary metabolites, including tannins, saponins, phenols, alkaloids, carbohydrates, cardiac glycosides, flavonoids, terpenoids, and steroids, while anthraquinones were absent. The antitrypanosomal activity was rigorously evaluated using a 96-well microtiter plate assay across a broad concentration range of 31.25–500 mg/mL. Parasite motility was monitored microscopically at 5-minute intervals over a 60-minute incubation period. The aqueous extract demonstrated a pronounced, concentration-dependent trypanocidal effect. Complete cessation of parasite motility was achieved at 45 minutes for the highest concentration (500 mg/mL), at 55 minutes for 250 mg/mL, and at 60 minutes for 125 mg/mL. Lower concentrations (62.5 and 31.25 mg/mL) exhibited progressively reduced efficacy. Assay validity was confirmed using diminazene diaceturate as the positive control and phosphate-buffered saline as the negative control. These compelling results indicate that C. glutinosum harbours bioactive constituents with promising antitrypanosomal activity, thereby scientifically validating its ethnomedicinal use and underscoring its potential as a valuable source of novel trypanocidal lead compounds for future drug development.